Differing mechanisms of atrial fibrillation in athletes and non-athletes: alterations in atrial structure and function. (5th August 2020) - Trivedi, Siddharth J; Claessen, Guido; Stefani, Luke; Flannery, M Darragh; Brown, Paula; Janssens, Kristel; Elliott, Adrian; Sanders, Prashanthan; Kalman, Jonathan; Heidbuchel, Hein; Thomas, Liza; La Gerche, Andre
Abstract: Aims: Atrial fibrillation (AF) is more common in athletes and may be associated with adverse left atrial (LA) remodelling. We compared LA structure and function in athletes and non-athletes with and without AF. Methods and results: Individuals (144) were recruited from four groups (each n  = 36): (i) endurance athletes with paroxysmal AF, (ii) endurance athletes without AF, (iii) non-athletes with paroxysmal AF, and (iv) non-athletic healthy controls. Detailed echocardiograms were performed. Athletes had 35% larger LA volumes and 51% larger left ventricular (LV) volumes vs. non-athletes. Non-athletes with AF had increased LA size compared with controls. LA/LV volume ratios were similar in both athlete groups and non-athlete controls, but LA volumes were differentially increased in non-athletes with AF. Diastolic function was impaired in non-athletes with AF vs. non-athletes without, while athletes with and without AF had normal diastolic function. Compared with non-AF athletes, athletes with AF had increased LA minimum volumes (22.6 ± 5.6 vs. 19.2 ± 6.7 mL/m 2, P  = 0.033), with reduced LA emptying fraction (0.49 ± 0.06 vs. 0.55 ± 0.12, P  = 0.02), and LA expansion index (1.0 ± 0.3 vs. 1.2 ± 0.5, P  = 0.03). LA reservoir and contractile strain were decreased in athletes and similar to non-athletes with AF. Conclusion: Functional associations differed between athletes and non-athletes with AF, suggesting different pathophysiological mechanisms. Diastolic dysfunction and reduced strain defined non-athletes with AF. Athletes had low atrial strain and those with AF had enlarged LA volumes and reduced atrial emptying, but preserved LV diastolic parameters. Thus, AF in athletes may be triggered by an atrial myopathy from exercise-induced haemodynamic stretch consequent to increased cardiac output. Graphical Abstract: